Impact of myristic acid on novel designed manifold assimilated with domestic solar water heater: An experimental approach - Chopra K.; Tyagi V.V.; Popli S.; Kumawat P.; Pandey P.; Kumar Pathak S.; Mansor M.; Pandey A.K. (Elsevier Ltd, 2025)
In this study, myristic acid as heat storage material was assimilated with a novel designed manifold of evacuated tube solar collector (EVTSC). The foremost advantage of this design is that the integration of myristic acid in the manifold does not affect the vacuum tube's strength and does not occupy extra roof space. Also, the advantageous thermal and chemical properties of myristic acid improve the performance of the system. The proposed system was tested for two different charging operations of storage material i.e. half-day charging operation and whole-day charging operation for water flow of 0.066, 0.133, and 0.20 LPM (liter per minute). These charging operations were selected to optimize the performance of the proposed system for daytime and nighttime hot water demand. The heat transfer analysis of the proposed system during both charging operations is also determined and compared. In addition to this, the machine learning approach is used to predict the hot water temperature. Concerning experimental results, the daily efficiency during HD-CHO is almost 62.42 %, 69.17 %, and 79.12 % respectively for the water flow of 0.066, 0.133, and 0.20 LPM. Whereas, during WD-CHO, daily efficiency was approximately 71.49 %, 80.42 %, and 85.21 % respectively for corresponding flow rates. Furthermore, the daily efficiency of the proposed system during HD-CHO and WD-CHO is found to be 42.85 % and 61 % higher than conventional systems. The higher and lower flow rates during both charging operations are recommended in terms of high daily efficiency and high hot water temperature respectively. Hence, the proposed system is designed to improve thermal performance, fulfill the hot water demand during late evening time, and decrease the overheating concern as compared to the conventional one. ? 2024 Elsevier Ltd